Investigation of car surveillance using GPS and GSM system based on google maps - Mohammed, Alhamzah Taher (International Journal of Engineering and Technology, 2018)
This paper initially surveys about car tracking organization and then investigate car surveillance using Global System for Mobile Communi-cation (GSM) and Geographical Positioning System (GPS). Nowadays, widespread GSM systems motivate many innovative applications such as location tracking and monitoring of car and children. These systems demonstrate the object is moving path by user cell phone or personal computer via mobile or internet networks. One of the more interesting technology is GPS which is used in many applications for tracking the vehicle monitoring and saving a possible record of all activity of driver and car services. The Google maps could support this technology by providing the online services of routing. This research includes the hardware part and comprises the GSM, GPS and Google maps with an efficient microcontroller. The software part represents the interface of the required module with web services for the proposed system and provides the platform for more enhancements in future requirements. The implementation results show that the objects are being tracked with minimum monitoring error and accurate track.